The role of the specific strength test in handball performance: exploring differences across competitive levels and age Groups - Chirosa-Ríos, L. J.; Chirosa-Ríos, I. J.; Martínez-Marín, I.; Román-Montoya, Y.; Vera-Vera, J. F. (Sensors, 2023)
The aim of this study was to determine if specific physical tests are sufficiently discriminant to differentiate players of similar anthropometric characteristics, but of different playing levels. Physical tests were conducted analyzing specific strength, throwing velocity, and running speed tests. Thirty-six male junior handball players (n = 36; age 19.7 ± 1.8 years; 185.6 ± 6.9 cm; 83.1 ± 10.3 kg; 10.6 ± 3.2 years of experience) from two different levels of competition participated in the study: NT = 18 were world top-level elite players, belonging to the Spanish junior men`s national team (National Team = NT) and A = 18 players of the same age and anthropometric conditions, who were selected from Spanish third league men`s teams (Amateur = A). The results showed significant differences (p < 0.05) between the two groups in all physical tests, except for two-step-test velocity and shoulder internal rotation. We conclude that a battery combining the Specific Performance Test and the Force Development Standing Test is useful in identifying talent and differentiating between elite and sub-elite players. The current findings suggest that running speed tests and throwing tests are essential in selecting players, regardless of age, sex, or type of competition. The results shed light on the factors that differentiate players of different levels and can help coaches in selecting players.